Biofuel production from spent coffee grounds via lipase catalysis. Issue 3 (1st February 2018) - Karmee, Sanjib Kumar; Swanepoel, Wian; Marx, Sanette
ABSTRACT: Lipases namely Mucor miehei, Pseudomonas cepacia, Rhizopus delemar, Geotrichum candidum, Candida rugosa, Porcine pancreas- II, Pseudomonas fluorescence, and Candida antarctica lipase-B (Novozyme-435) were employed for biodiesel synthesis from spent coffee oil. Around 96% oil-to-biodiesel conversion was obtained using Novozyme-435 as a catalyst at 1:5 oil-to-methanol molar ratio and 40ºC. Total spent coffee grounds generated at the North-West University, Potchefstroom Campus (NWU PC) was estimated which could be used to produce 162 L of biodiesel. A waste valorization strategy was devised for converting organic wastes produced at the NWU PC to bioenergy.